Are rodents a source of biotic resistance to tree invasion in Pampean grasslands? Tree seed consumption under different conditions - Muschetto, Emiliano (2015)
Biotic resistance has been invoked as a major barrier to woody species invasion, although the role of resident generalist consumers and their interaction with seed availability in a local community has received little attention.We assessed tree seed consumption by rodents under two different scenarios: (i) We documented in field spatio-temporal patterns of seed predation by native rodents on two exotic tree species, Gleditsia triacanthos or ‘honey locust’ and Robinia pseudoacacia or ‘white locust’ (family Leguminosae), in five grassland habitats of the Inland Pampa, Argentina. (ii) We conducted laboratory feeding trials to evaluate tree seed consumption in the presence (cafeteria-style feeding trials) and in the absence (non-choice feeding trials) of alternative food supplies. Seed predation was generally higher for Robinia than for Gleditsia seeds, both in field and laboratory conditions. For both tree species, seed predation varied between habitats and seasons and was higher in the native tussock grassland than in the remaining studied communities, whereas the crop field showed the lowest levels of consumption along with the absence of captured rodents. Seed consumption of Gleditsia and Robinia among the four grassland communities (which did not differ in rodent abundance) was negatively associated with the availability of alternative food. Laboratory feeding trials showed a higher consumption of Gleditsia seeds in the non-choice than in the cafeteria-style feeding trials, while the consumption of Robinia seeds did not differ in the absence or presence of alternative seeds. These patterns indicate that the contribution of resident granivores to invasion resistance might depend on colonizer species identity, recipient community type and season of the year. We suggest that rodent preferences for different invader seeds will interact with the availability of alternative food in the local habitat in influencing the amount of predator-mediated biotic resistance to invasion.